Surveillance and Prevalence of Canine Reproductive Disorders in Gujarat - Gupta, AK; Dhami, AJ; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The epidemiological surveillance of canine reproductive disorders was carried out based on total 21852 clinical cases (9159 at the College Clinic, Anand, and 12693 at Polyclinic, Vadodara) attended in dogs over three years. Among them, the overall 486 (2.22 %) and 85 (0.39 %) cases were of gynecological and andrological nature, respectively. Amongst the gynaecological cases, the highest incidence was of pyometra (23.25 %), followed in descending order by mammary tumours (22.22 %), pregnancy diagnosis (16.25 %), elective sterilization (9.88 %), CTVG (7.61 %), proestrus bleeding (5.97 %), pseudo-pregnancy (3.06 %), misalliance (2.67 %), anestrus (2.26 %), dystocia (1.65 %), abortion (1.03 %) and Cesarean (0.82%). Among the andrological cases, the highest cases were of venereal granulomas (31.76 %) followed in descending order by scrotal dermatitis (18.82 %), castration (12.94 %), orchitis (7.06 %), cryptorchidism, paraphimosis and balanoposthitis (5.88 % each), prostatic hyperplasia and testicular tumor (4.70 % each) and testicular hyperplasia (2.35 %). The breed most prone to gynecological disorders was non-descript (51.65 %), Pomeranian (16.25 %), German Shepherd, Labrador (6.79 % each) and Doberman (5.97 %). Maximum cases were in the young age group of 0-5 years (51.02 %), followed by the middle age group of 6-10 years (27.57 %) and older bitches of 11-15 years of age (20.58 %). The major clinical modalities and their management strategies adopted have also been summarized. The results signified the importance of life-threatening diseases like pyometra, mammary tumors, and CTVG in pet dogs in urban areas of middle Gujarat.